(untitled) (Inovasi, 2026)
Haji Medan General Hospital faces several challenges related to energy management, namely high energy consumption. Hospitals require large amounts of energy for various purposes, including lighting, cooling, medical equipment, and supporting facilities. High energy use is often not balanced with adequate efficiency practices, resulting in high operational costs. Therefore, this study aims to see the level of energy consumption intensity at RSU Haji Medan. The research method used in this study uses a Qualitative method by tracing several documents related to the study such as monthly electricity consumption in the last three years, building area exposed to energy, building plans, and photos of building facades. The analysis results show that RSU Haji Medan has succeeded in maintaining very efficient energy consumption during the period 2021-2023 with an IKE of 114 kWh/m²/year in 2021, increasing to 137 kWh/m²/year in 2022, and reaching 177 kWh/m²/year in 2023. Despite the increase in energy consumption, the IKE value is still below the threshold of 180 kWh/m²/year, which is included in the Very Efficient category. RSU Haji Medan is still far below the average global hospital energy consumption (380 kWh/m²/year), indicating significant success in energy management. Analysis of the readiness of implementing an energy management system based on ISO 50005:2021 shows that RSU Haji Medan is still in the early stages in several aspects, such as energy review, setting energy goals and targets, and developing energy competencies and awareness. To maintain the very efficient category, recommendations need to be made by RSU Haji Medan, namely the need to continue to monitor IKE routinely and strictly, strengthen the Energy Management System, optimize the use of energy-saving technology, and energy awareness training and campaigns and provide a budget to support it.